The Influence of Land and Building Acquisition Tax (BPHTB) and Land and Building Tax - Rural and Urban (PBB-P2) on Regional Financial Independence in Regency/City of West Java Province, Year 2021 to 2023 - Nolarita, Sofi Windi; Winarso, Eddy (Majapahit Journal of Islamic Finance and Management, 2025)
This study analyses the influence of Land and Building Acquisition Tax (BPHTB) and Rural and Urban Land and Building Tax (PBB-P2) on regional financial independence in regencies/cities in West Java Province. The approach used was a mixed-methods approach with a sequential explanatory design, beginning with quantitative analysis of secondary data from 2021 to 2023. This phase was followed by qualitative analysis through in-depth interviews with local government officials. The quantitative results indicate that BPHTB and PBB-P2 have a positive and significant influence on the level of regional financial independence. Qualitative findings indicate that these two taxes are significant not just for their ability to generate income but also for how they are managed. Challenges in managing BPHTB and PBB-P2 encompass target establishment affected by non-technical variables, unpredictable revenue potential, uncollectable receivables, data inconsistencies, insufficient fair value benchmarks, and constrained collection authority for national strategic initiatives. Implemented strategies encompass transaction value verification according to NJOP, revaluation of taxable assets, digitalisation of services, public engagement, fiscal incentives, and collaborations with third parties. This study emphasises the importance of effective regional tax management to strengthen fiscal capacity and reduce dependence on transfer funds.